Bifacial Photovoltaics 2021: Status, Opportunities and Challenges - Radovan Kopecek; Joris Libal (Energies, 2021)
In this paper we summarize the status of bifacial photovoltaics (PV) and explain why the move to bifaciality is unavoidable when it comes to e.g., lowest electricity generation costs or agricultural PV (AgriPV). Bifacial modules—those that are sensitive to light incident from both sides—are finally available at the same price per watt peak as their standard monofacial equivalents. The reason for this is that bifacial solar cells are the result of an evolution of crystalline Si PV cell technology and, at the same time, module producers are increasingly switching to double glass modules anyway due to the improved module lifetimes, which allows them to offer longer product warrantees. We describe the general properties of the state-of-the-art bifacial module, review the different bifacial solar cells and module technologies available on the market, and summarize their average costs. Adding complexity to a module comes with the increase of possible degradation mechanisms, requiring more thorough testing, e.g., for rear side PID (Potential Induced Degradation). We show that with the use of bifacial modules in fixed tilt systems, gains in annual energy yield of up to 30% can be expected compared to the monofacial equivalent. With the combination of bifacial modules in simple single axis tracking systems, energy yield increases of more than 40% can be expected compared to fixed tilt monofacial installations. Rudimentary simulations of bifacial systems can be performed with commercially available programs. However, when more detailed and precise simulations are required, it is necessary to use more advanced programs such as those developed at several institutes. All in all, as bifacial PV—being the most cost-effective PV solution—is now becoming also bankable, it is becoming the overall best technology for electricity generation.